Social Change in Sociological, Pedagogical, Psychological, Economic, and Religious Views - Arrasid Siregar, Makmun (Pusdikra-Publishing.com, 2024)
The purpose of this paper is to discuss Social Change in Sociological, Pedagogical, Psychological, Economic, and Religious Reviews. The conclusion of this paper is that Indonesia, as a country with a Muslim majority, shows a wide religious diversity with a Muslim majority reaching 87.18% of the total population in 2010. Most Muslims are concentrated on the island of Java, while other religions such as Christianity, Catholicism, Hinduism, Buddhism, and Confucianism have adherents spread across various regions, each with different proportions. Although Indonesia faces challenges in maintaining tolerance and harmony between religions, the attitude of Islam as rahmatan lil 'alamin (blessing for the universe) helps create peaceful relations among adherents of various religions. Efforts to strengthen this harmony are important in facing the challenges of claims to religious truth, fanaticism, and teachings to spread religion, which if managed wisely through dialogue and interfaith cooperation, can maintain peace amidst existing pluralism.